ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN (Studi Pada Dinas Pendapatan, Pengelolaan Keuangan dan Aset Kota Probolinggo) - Pertiwi, Rizka Novianti (Jurnal Mahasiswa Perpajakan, 2014)
Land and Building Tax Transitional Rural and Urban throughout the Regency/ City Government conducted begin no later than January 1, 2014. Probolinggo city is one of cities that implemented tax on land and building be the Local Taxes in 2013. Law No. 28 of 2009 on Regional Taxes and Levies Tax on Land and Building mandates previously Tax Center is now a local tax. The method used is descriptive research.Â  The results indicate the effectiveness of land and building tax collection in Probolinggo City less effective because for 6 years from 2008-2013 have not reached the predetermined income target. Low income receipt in 2010 amounted to 72.12% with less effective criteria. While the highest income realization in 2013 amounted 83.48% with criteria quite effective. The increasing of land and building tax income in 2013 due the transition of land and building tax into Local Taxes. In the other hand, taxes socialization from fiscus increase tax compliance. In an effort to improve the land and building tax income in Probolinggo city need to repeat data collection on Land and Building Tax Objects by adjusting the market price and the current economy. Keyword: Regional Taxes, Land and Building Tax Transition, and Land and Building Tax